Modeling and optimization of dynamic isothermal compressibility features on flowability of Canarium schweinfurthii Engl nutshell powder - James Chinaka Ehiem; Victor Ifeanyichukwu Obiora Ndirika; Udochukwu Nelson Onwuka; Raghavan Vijayan (Research in Agricultural Engineering)
The compressibility features (bulk density, tapped bulk density, porosity, coefficient of compressibility and Hauser ratio) of Canarium schweinfurthii engl. nutshell powder as it affects flowability during densification process were investigated. Three different moisture contents (10.13, 15.07 and 20.11% wet basis; w.b.) and particle sizes of 0.659 7, 1.26 and 2.05 mm were considered at pressure range of 2 to 10 MPa. The compressibility relationship with the factors were modelled and the optimum flow conditions were also determined. The obtained results showed that particle size and moisture content had incremental influence on the compression features studied except moisture content on bulk density. The compressibility of the nut shell powder increased from 17.44 to 28.18% and decreased from 29.41%to 18.79% as moisture content and particle size increased respectively. Medium particle size had the least Hausner ratio (1.16) and the best flow behaviour than other sizes for all the studied moisture contents. The linear model developed and its features had significant relationship with compressibility. The optimum values of pressure, moisture content and particle size required to achieve 17.45% compressibility for good flow are 4.88 MPa, 10.91% and 0.863 8 mm respectively.